Optimizing the management of patients with spinal myeloma disease. (17th July 2015) - Molloy, Sean; Lai, Maggie; Pratt, Guy; Ramasamy, Karthik; Wilson, David; Quraishi, Nasir; Auger, Martin; Cumming, David; Punekar, Maqsood; Quinn, Michael; Ademonkun, Debo; Willis, Fenella; et al.
Summary Myeloma is one of the most common malignancies that results in osteolytic lesions of the spine. Complications, including pathological fractures of the vertebrae and spinal cord compression, may cause severe pain, deformity and neurological sequelae. They may also have significant consequences for quality of life and prognosis for patients. For patients with known or newly diagnosed myeloma presenting with persistent back or radicular pain/weakness, early diagnosis of spinal myeloma disease is therefore essential to treat and prevent further deterioration. Magnetic resonance imaging is the initial imaging modality of choice for the evaluation of spinal disease. Treatment of the underlying malignancy with systemic chemotherapy together with supportive bisphosphonate treatment reduces further vertebral damage. Additional interventions such as cement augmentation, radiotherapy, or surgery are often necessary to prevent, treat and control spinal complications. However, optimal management is dependent on the individual nature of the spinal involvement and requires careful assessment and appropriate intervention throughout. This article reviews the treatment and management options for spinal myeloma disease and highlights the value of defined pathways to enable the proper management of patients affected by it.